The Role of Moving Teachers in Forming Students’ Character Throught the Pancasila Student Profile Strengthening Project (P5) in History Learning - Gusniati, Liza; Nurdin, Buchari; Nazmi, Ranti (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research is motivated by the existence of a driving teacher who is tasked with leading learning in encouraging the growth and development of a holistic, active, and proactive learning system in shaping student character through the Pancasila Student Profile Strengthening Project at SMAN 5 Sijunjung. This research aims to describe the role of driving teachers in developing student character-building programs through the Project for Strengthening Pancasila Student Profiles in History Learning and the role of driving teachers in implementing student character-building programs through the Strengthening Pancasila Student Profile Project. The method used in this research is descriptive qualitative, namely explaining the phenomenon of social reality which is complete, complex, dynamic, meaningful, and interactive, expressed rationally, empirically, and systematically. The results of this research show that the driving role of teachers in shaping student character, the role of driving teachers in preparing student character-building programs through P5 is in the form of designing programs, dividing each other's tasks with other teachers, and helping create activity programs with teachers at school.